Online Catering Collaboration System - Nur Hafizah, Ghazali (2010)
Nowadays, internet has become a medium that has a superb marketing solution. With it fast, easy to use and cheap in term of operational cost a marketing process can be done with just a click. E-commerce has significantly affected the business world and will continue to be important. Catering services is one of the industries that have been affected by the rapid growth of e-commerce. From literatures, it is observed that there are still many challenges to be tackled in e-commerce applications. One of the challenges in e-commerce especially in online catering services is lack of integration, flexibility and information sharing between three major entities involved which are customer, caterer and supplier. Hence, this study intends to close the gaps that exist between these three entities which prevent them to move forward.